Urban movements and democratization in the city: a proposal for analysis - Imanol Telleria Herrera; Igor Ahedo Gurrutxaga (Revista Española de Ciencia Política, 2016)
This article is based on an in-depth study of three cases (Barcelona, Pamplona and Bilbao) and it tries to present a more current portrayal of urban movements from a theoretical perspective. To that aim, it brings into the same analytical framework the contributions of both the American and European schools study of social movements. A proposal is presented that gives applied content to this sui generis political actor by taking into account variables such as the structure of political opportunity (EOP), organizational forms, repertoires of action and discursive frameworks. We believe that urban movements have evolved gaining more access to the political system. They have benefited from the new opportunities offered by local governance (EOP) and have encouraged participatory processes. These participatory processes, built from the communitarian methodology (repertoires) are intended to promote a democratic management of the city (speech), by means of network logic (organization) which seeks to restructure the society, as a first step towards increasing their influence on urban policies.